Factors influencing the implementation of evidence‐based guidelines for osteoarthritis in primary care: A systematic review and thematic synthesis. (30th January 2020) - Swaithes, Laura; Paskins, Zoe; Dziedzic, Krysia; Finney, Andrew
Abstract: Introduction: Implementation of evidence‐based health guidelines in primary care is challenging. This systematic review aimed to synthesize qualitative evidence that investigates the factors influencing the implementation of evidence‐based guidelines for osteoarthritis in primary care. Methods: A systematic review of qualitative studies. MEDLINE, EMBASE, CINAHL, HMIC, PsychINFO, Web of Science and Assia were searched (from 2000 to March 2019). The methodological quality of the included studies was assessed by two independent reviewers. Data were analyzed and synthesized using thematic synthesis. Results: 1612 articles were screened and four articles with a total of 87 participants (46 patients, 28 GPs, 13 practice nurses) were included. Three of the studies were conducted in England within the context of an implementation trial and one was conducted in the Netherlands. The thematic synthesis revealed three overarching themes. Best practice was not enough to achieve 'buy‐in' to implementation but a range of tacit motivators to implementation were identified. Healthcare professionals used patient reasons to justify engaging or not engaging with implementation. Engaging with the whole practice was important in achieving implementation. A disconnect between research and 'real‐world' primary care practice influenced long‐term implementation. Conclusions: Despite the relative paucity of current evidence, this systematic review has identified a series of possible disconnects may impact uptake of interventions to improve osteoarthritis care, existing between clinicians and patients, researchers and clinicians, clinicians and guidelines and within general practice itself. There remains a need to further explore the experiences of key stakeholders, including patients involved in implementation for osteoarthritis in primary care.